Membangun Imajinasi Wisatawan melalui Pengalaman Perjalanan di Kawasan Wisata Warisan Budaya - Rista, Rista; Sinangjoyo, Nikasisus Jonet; Damasdino, Fian (Sekolah Tinggi Pariwisata AMPTA, 2019)
This research aims to build the imagination of tourists through travel experiences in the cultural heritage tourism area. The author analyzes the imagination gained by tourists using seven factors: lodging and dining facilities, internal accessibility, nearby attractions, external accessibility, safety and emergency systems, on-site attractions and the provision of information services. Data collection by observation, interview, FGD, documentation, and literature study through descriptive qualitative data analysis. The results showed that the myth of the bathing pool was the most dominant in building the imagination of tourists and became the main reason for tourists visiting Tamansari. Generally tourists can imagine the myths conveyed by tour guides and tend to portray Tamansari as a beautiful place in the past. Travel experiences gained by tourists during a tour in Tamansari are myths, history, and activities at the location. The most dominant factors that build the imagination of tourists through travel experience are (1) external accessibility (2) attraction factors in places where myths (3) nearby attractions